PENGAPLIKASIAN BIM 5D UNTUK PEKERJAAN ARSITEKTUR PADA PROYEK GEDUNG IGD RSUD WARAS WIRIS BOYOLALI - Canggih Gilang Pradana H. S; Ramadhan Widy Pratama; Rainy Shinta Nur Halimah (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2023)
Building Information Modelling (BIM) is a system for digitizing data processing that can help work in the construction industry run more effectively and efficiently. One type of BIM is 5D BIM. 5D BIM has the function of determining the take-off quantities and analyzing the costs of a building. An example of 5D BIM is Cubicost. Cubicost BIM is a BIM from the Glodon company that allows you to calculate work volumes in a detailed and precise way. In this research, the case study presented is an architectural work on the Waras Wiris Boyolali Hospital Emergency Building Construction Project. The architectural section was selected because architectural works play an important role in nominal terms, so the determination of volume greatly influences construction costs. This research uses Cubicost TAS and TRB software. Cubicost Software's volume results have also been validated so that they show a 99% correlation figure with volume obtained from conventional calculations. Based on the research carried out, the cost of using Cubicost software for architectural works in the Waras Wiris Boyolali Emergency Hospital Building Construction Project is Rp. 1.695.645.165,47. Using the Cubicost software also produces an efficiency of 11.550% on RAB from the consultant.